Improvement of superoxide dismutase activity using experimental design and radical promoters. Issue 5 (3rd September 2017) - Ünlü, Ayşe Ezgi; Takaç, Serpil
ABSTRACT: The culture conditions of Rhodotorula glutinis were optimised to obtain high activity of superoxide dismutase (SOD) enzyme, which is an important member of the antioxidant defence system. By the use of glycerol as a carbon source, which is a by-product of biodiesel production, 2.40 U of SOD activity was achieved under the optimised conditions found by Central Composite Design (pH = 5.47, T = 33.9 °C and 16.50 g L −1 glycerol). In order to provide a further increase in SOD activity, different types of radical promoters were tested and the highest enzyme activity was achieved with methyl viologen, 21.57 U mg −1 protein with a 1.6-fold increase. The effect of dissolved oxygen (DO) on SOD activity was also investigated employing different operational strategies in bioreactors. SOD activity was found to be induced only when high DO concentration was supplied starting from the beginning of the cultivation where the activity of 75 U mg −1 protein was obtained.